Improving the Processes of Integration of Enterprises and Educational Institutions with Human Resources Consumers - Abdalova S.R. (Academia One Publishing, 2023)
this article will talk about issues of improvement of integrative processes among enterprises and educational institutions, the system of an enterprise - educational institution, directions of improvement of integrative processes.
Keywords: education; didactic; method